2019
DOI: 10.3390/ijms20092072
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Doped TiO2 Activated by X-Ray Irradiation for the Generation of Reactive Oxygen Species to Enhance Photodynamic Therapy in Tumor Treatment

Abstract: Traditional photodynamic therapy (PDT) is limited by the penetration depth of visible light. Although the light source has been changed to near infrared, infrared light is unable to overcome the penetration barrier and it is only effective at the surface of the tumors. In this study, we used X-ray as a light source for deep-seated tumor treatment. A particle with a narrow band gap when exposed to soft X-rays would produce reactive oxygen species (ROS) to kill tumor cell, with less damage to the normal tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…At low concentrations, ROS act as signaling molecules involved in promoting cell survival and proliferation, whereas at high concentrations, they induce programmed cell apoptosis and necrosis (35,36). Previously published studies noted that the excessive accumulation of high levels of ROS may trigger cancer cell apoptosis and death and may inhibit cancer progression during enhanced oxidative stress injury (37)(38)(39). Thus, it was concluded that, in the process of cancer progression, the analysis of ROS level fluctuation may be of importance for cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…At low concentrations, ROS act as signaling molecules involved in promoting cell survival and proliferation, whereas at high concentrations, they induce programmed cell apoptosis and necrosis (35,36). Previously published studies noted that the excessive accumulation of high levels of ROS may trigger cancer cell apoptosis and death and may inhibit cancer progression during enhanced oxidative stress injury (37)(38)(39). Thus, it was concluded that, in the process of cancer progression, the analysis of ROS level fluctuation may be of importance for cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…TiO 2 :C. Chun-Chen Young and his co-authors [36] investigated nanoparticles with a narrow bandgap and ROS generation under the influence of soft X-ray radiation to destroy tumor cells with less damage to healthy tissues. In this experiment, anatase lattice was doped with C, and then it was activated by X-rays to produce more reactive oxygen species and destroy tumor cells.…”
Section: Types Of Photosensitizersmentioning
confidence: 99%
“…In addition, the in vivo study also confirmed a low A459 cancer cells viability by ROS generation. Overall, TiO 2 :C inhibited cancer growth efficiently and improved PDT effects (49).…”
Section: Titaniummentioning
confidence: 99%